Comparison of Five Different Criteria for Diagnosis of Subclinical Hypothyroidism in a Large-Scale Chinese Population - Zheng, Yan-song; Dong, Sheng-yong; Gong, Yan; Wang, Jia-hong; Wang, Fei; Zeng, Qiang (Frontiers in Endocrinology, 2022)
Background Several different criteria for subclinical hypothyroidism (SCH) have been used in the literature, but the performance of these criteria was unknown. Objective This retrospective study was to evaluate the diagnostic criteria for SCH. Methods Eligible participants were based on centration of thyroglobulin antibodies (TG-Ab), thyroid peroxidase antibodies (TPO-Ab), and five thyroid-related hormones including total thyroxine (TT4), total triiodothyronine (TT3), free thyroxine (FT4), free triiodothyronine (FT3), and thyroid-stimulating hormone (TSH). Euthyroid individuals were identified via specific criteria. Five different SCH diagnostic criteria were compared based on the distributions of those indicators. An appropriate TSH cut-off value was reconsidered. Results The study included 145,015 participants. The number of SCH cases diagnosed using criterion 5 was significantly different compared to the cases diagnosed using criteria 1-4 (P<0.05) and had the highest positive proportions of TG-Ab and TPO-Ab. Analysis of 60,515 subjects with normal other thyroid hormones revealed a median TSH concentration of 2.04 mIU/L, and the P2.5–P97.5 CI was 0.48-7.03 mIU/L. When the threshold for TSH elevation was elevated from ≥4.5 mIU/L to ≥6.50 mIU/L, the number of diagnosed SCH cases decreased from 7.30% to 2.09% and the proportions of positive TG-Ab and TPO-Ab increased from 23.69% and 24.07% to 33.75% and 35.06%, respectively (P<0.01). Conclusions Combination of an elevated TSH and normal TT3, TT4, FT3, and FT4 concentrations is a must for the diagnosis of SCH. A new TSH threshold should be identified for better patient monitoring and management, according to the real-world characteristics of TSH distribution in Chinese population.